2014
DOI: 10.1111/desc.12142
|View full text |Cite
|
Sign up to set email alerts
|

Effects of classroom bilingualism on task‐shifting, verbal memory, and word learning in children

Abstract: We examined the effects of classroom bilingual experience in children on an array of cognitive skills. Monolingual English-speaking children were compared with children who spoke English as the native language and who had been exposed to Spanish in the context of dual-immersion schooling for an average of two years. The groups were compared on a measure of non-linguistic task-shifting; measures of verbal short-term and working memory; and measures of word-learning. The two groups of children did not differ on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
97
3
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(119 citation statements)
references
References 128 publications
10
97
3
5
Order By: Relevance
“…The existing literature on bilingual word learning is rather sparse, and it is not entirely clear whether word-learning tasks reduce the gap between bilingual and monolingual performance. In fact, while some studies have reported higher levels of word-learning performance in monolingual participants (Wilkinson & Mazzitelli, 2003), other studies have shown similar levels of word-learning performance in monolinguals and bilinguals (Kan & Sadagopan, 2014), and yet another set of studies has yielded bilingual advantages on word-learning and/or fast-mapping tasks (Kan et al, 2014; Kaushanskaya et al, 2014). Research with monolingual children has demonstrated that the ability to learn novel words is strongly associated with the child’s existing language knowledge so that children with better vocabulary skills are better able to learn novel words (e.g., Ellis Weismer & Evans, 2002; Gray, 2003, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The existing literature on bilingual word learning is rather sparse, and it is not entirely clear whether word-learning tasks reduce the gap between bilingual and monolingual performance. In fact, while some studies have reported higher levels of word-learning performance in monolingual participants (Wilkinson & Mazzitelli, 2003), other studies have shown similar levels of word-learning performance in monolinguals and bilinguals (Kan & Sadagopan, 2014), and yet another set of studies has yielded bilingual advantages on word-learning and/or fast-mapping tasks (Kan et al, 2014; Kaushanskaya et al, 2014). Research with monolingual children has demonstrated that the ability to learn novel words is strongly associated with the child’s existing language knowledge so that children with better vocabulary skills are better able to learn novel words (e.g., Ellis Weismer & Evans, 2002; Gray, 2003, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Yow and Markman (2015) used a word learning test that included a Theory of Mind component. Because there is evidence for a bilingual advantage in word learning (Kaushanskaya et al, 2014), better performance on the word learning test might not reflect a bilingual advantage in Theory of Mind per se. Due to this confound, this study was not sufficient data to compute an effect size and were reported in a journal (k = 13) or a dissertation (k = 3).…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…Kaushanskaya, Gross, and Buac (2014) examined the effects of classroom bilingualism on executive functioning as measured by task shifting as well as measures of verbal memory and word learning. For task switching, they used the Dimensional Change Card Sorting Task (Frye, Zelazo, and Palfai 1995), a task previously found to be performed better by bilingual than monolingual preschool children (Bialystok 1999).…”
Section: Other Academic and Cognitive Achievementsmentioning
confidence: 99%
“…In these three examples, children who were assigned to groups either because of ethnicity (Mezzacappa 2004) or education program (Esposito and Baker-Ward 2013; Kaushanskaya, Gross, and Buac 2014) were compared to controls for their performance on executive function tasks. A different approach is to use exposure to bilingual education as a scaled variable to determine if it is associated with executive function performance and thereby avoid between-groups comparisons.…”
Section: Other Academic and Cognitive Achievementsmentioning
confidence: 99%